PENAMBAHAN EKSTRAK DAUN KELOR TERHADAP PEMBUATAN BOMBOLONI UNTUK MEMBANDINGKAN WARNA MELALUI UJI ORGANOLEPTIK - Putri Bintang; Lence Ristiani; Helmi Susanti; Muflih Martua Tanjung; Adrian Topano (Universitas Bhinneka PGRI, 2024)
Bomboloni are Italian donuts that are round in shape without a hole in the middle. Bomboloni is made from the basic ingredients of flour and egg dough, then it is made by frying with various jam fillings. Especially the bomboloni in this study where moringa leaf extract was added in the preparation of the bomboloni dough from the previous one. Moringa thrives in Indonesia because the climate and soil are very supportive for the growth of Moringa. Moringa contains various phytochemical compounds, including tannins, flavonoids, saponins, and alkaloids, all of which are antioxidants. Moringa leaves also contain high antioxidants, some of the main phenolic bioactive compounds are the flavonoid group. To determine the effect of adding moringa leaves to bomboloni processed products by means of organoleptic methods. The research method used was a quantitative approach, experiments and organoleptic tests using a simple randomized design with four experimental units and five different treatments. The criteria tested were aroma, taste, texture and color. Based on the research results obtained from four experimental units and five different treatments that the best color is 15% so the best overall is the addition of 15% moringa extract.